Introduction: Looking Back - Claxton, Patricia (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2000)
AbstractA brief historical overview of the ATTLC / LTAC, with emphasis on the very beginnings.Comparison between the limited range of activities then and the abundance now. A glance forward. Recall of key names and thanks. Dedication.